QDPR homologues in Danio rerio regulate melanin synthesis, early gliogenesis, and glutamine homeostasis - Breuer, Maximilian; Guglielmi, Luca; Zielonka, Matthias; Kölker, Stefan; Okun, Jürgen G.; Hoffmann, Georg F.; Carl, Matthias; Sauer, Sven; Opladen, Thomas (PLOS ONE, 2019)
Dihydropteridine reductase (QDPR) catalyzes the recycling of tetrahydrobiopterin (BH4), a cofactor in dopamine, serotonin, and phenylalanine metabolism. QDPR-deficient patients develop neurological symptoms including hypokinesia, truncal hypotonia, intellectual disability and seizures. The underlying pathomechanisms are poorly understood. We established a zebrafish model for QDPR deficiency and analyzed the expression as well as function of all zebrafish QDPR homologues during embryonic development. The homologues qdpra is essential for pigmentation and phenylalanine metabolism. Qdprb1 is expressed in the proliferative zones of the optic tectum and eye. Knockdown of qdprb1 leads to up-regulation of pro-proliferative genes and increased number of phospho-histone3 positive mitotic cells. Expression of neuronal and astroglial marker genes is concomitantly decreased. Qdprb1 hypomorphic embryos develop microcephaly and reduced eye size indicating a role for qdprb1 in the transition from cell proliferation to differentiation. Glutamine accumulation biochemically accompanies the developmental changes. Our findings provide novel insights into the neuropathogenesis of QDPR deficiency.